Analytical chemistry for the study of paintings and the detection of forgeries - Colombini, Maria Perla; Colombini, Maria Perla; Degano, Ilaria; Degano, Ilaria; Nevin, Austin; Nevin, Austin (Cultural heritage science, 2022)
Part I Approaches to the authentication of works of art -- The Eye versus Chemistry? From 20th to 21st Century Connoisseurship -- Scientific Study, Condition Challenges, and Attribution Questions in Yves Tanguy’s Oeuvre -- Analytical Approaches to the analysis of paintings: an overview of methods and materials -- Part II Characterization of paintings by digital techniques -- Visible and Infrared Reflectance Imaging Spectroscopy of Paintings and Works on Paper -- Automated Analysis of Drawings at the Stroke Level for Attribution and Authentication using Artificial Intelligence -- Part III Material Characterization of paintings by instrumental techniques -- Analytical pyrolysis of organic paint materials for authentication and attribution -- Direct and hyphenated mass spectrometry to detect glycerolipids and additives in paint -- Luminescence for the analysis of paintings; A. Nevin -- Analysis of natural and synthetic organic lakes and pigments by chromatographic and mass spectrometric techniques -- Raman analysis of inorganic and organic pigments -- Non-invasive and non-destructive examination of artists’ pigments, paints and paintings by means of X-ray imaging methods -- Microchemical Imaging of Oil Paint Composition and Degradation: State-of-the-Art and Future Prospects -- Part V Isotopic analysis for authentication -- Dating of artwork by radiocarbonjdas -- Lead Isotope ratios of lead white: from provenance to authentication.-Part V Case studies -- The role of technical study and chemical analysis on questions of attribution and dating of paintings and on easel painting conservation practice: Selected case studies -- Approaches to Current Issues with Art Forgery, Restoration and Conservation: Legal and Scientific Perspectives.